Foreign workers in South Korea - Su-Jin Lim (Portes: Revista mexicana de estudios sobre la Cuenca del Pacífico, 2010)
In today’s global age many people cross national borders in search of better work and more wages. According to IOM, more than 100 000 000 workers leave their homeland and migrate to another country for this reason. Europe and North America have already experienced increase in foreign labor for many decades but nowadays, it is very common to see foreign laborers in Asian countries. As the number of foreign laborers rapidly increased, however, so did many social problems in relation to these workers. No country is safe from or immune to such social problems in regards to the foreign workers especially with a much easier and more efficient transportation system. In case of South Korea, the history of foreign labor may not be as long as other nations but as of 2007, it boasts of more than 250 000 foreign laborers and is thus facing just as many social problems as well. In order to investigate such social issues, this article explores the history of foreign laborers and their current situation in South Korea. Furthermore, this artticle examines both internal and external factors which may have caused exponential growth of foreign labor market in South Korea in the past decade.